Paṭah khazānah : taẕkirah al-shuʻarāʼ - Muḥammad Hotak, fl. 1673-1730 (da I̤t̤tilāʻāto aw Kaltūr Wizārat, da Puṣto da Taqwiyī aw Inkishāf Amirīyat, 1975)
Biographical sketches of early Pushto poets; includes a selection from their works.